Optimalisasi Pelaksanaan Kurikulum Merdeka Belajar dalam Meningkatkan Mutu Pembelajaran di SMP Negeri 2 Torjun - Siti Farida; Moh Khorofi; Mutmainnah Mutmainnah (LP2M Institut Agama Islam Nazhatut Thullab Sampang, 2025)
The Merdeka Belajar Curriculum is an educational policy innovation launched to address post-pandemic learning challenges and to promote the strengthening of students' character and competencies. SMPN 2 Torjun is one of the educational institutions that began implementing this curriculum in the 2023 academic year. This study was conducted to explore how the optimization of planning, implementation, and evaluation of the Merdeka Curriculum contributes to improving the quality of learning at the school. The method used was a qualitative approach with a case study design. Data collection techniques included interviews, observation, and documentation, while data analysis employed Miles & Huberman’s interactive analysis model with source and technique triangulation. The findings reveal that: (First) the planning of the Merdeka Curriculum at SMPN 2 Torjun was carried out collaboratively by involving the principal, teachers, school committee, and the Department of Education. The category chosen for implementation was Mandiri Berubah (Independent Transition). (Second) the curriculum implementation was effective through student-centered learning strategies and the integration of the Projek Penguatan Profil Pelajar Pancasila (P5) as a means of character development. (Third) evaluation was conducted regularly through official meetings, principal supervision, and external oversight, with the aim of continuous improvement. Overall, the implementation of the Merdeka Curriculum has had a positive impact on enhancing the quality of learning, both academically and non-academically.